Analisis Fluktuasi Harga Udang Vannamei di Kabupaten Kolaka - Irwandi Irwandi; Masitah Masitah; Yuli Purbaningsih (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2023)
Kolaka Regency is an area that is the center of pond fishery production, including vannamei shrimp commodities. Some sub-districts in southern Kolaka that are the center of vannamei shrimp production are Pomalaa District, Tanggetada District and Watubangga District. As one of the fishery commodities with an export orientation, shrimp commodities are very vulnerable to price fluctuations. Apart from demand and supply factors, the price of production inputs can also affect the price of vannamei shrimp commodities indirectly, where when the price of production inputs increases, the amount of production will tend to decrease. The decrease in the amount of production will eventually have an impact on increasing the price of vannamei shrimp in the market as a result of a decrease in supply in the market. The purpose of this study is to determine the fluctuations in the price of vannamei shrimp in the South Kolaka area in 2017 – 2021 and to find out the price trend of vannamei shrimp in the South Kolaka area in 2017 – 2021. Data analysis performed using Two Stage Linear Square (2SLS) analysis. The results showed that shrimp prices in Kolaka Regency are very volatile. The price fluctuative is caused by the unstable amount of production in the market, where shrimp prices will tend to increase when the amount of production produced is smaller than market demand and it is known that the results of price trend analysis show that in the last 5 years (2017 to 2021), The price of vanname shrimp in Kolaka Regency continues to increase, where the price increase in the last 5 years is Rp 2,500 per kg.